Pembagian Harta Bersama (Gono Gini) Putusnya Perkawinan Karena Perceraian Pada Perkawinan Poligami - Syafrida Syafrida; Arihta Esther Tarigan; Hasudungan Sinaga (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Abstract Undang Nomor 1 Tahun 1974 tentang perkawinan menganut asas monogami terbuka pada prinsipnya seorang suami hanya boleh punya satu istri namun dibolehkan poligami asal memenuhi syarat dalam perundang-undangan. Perkawinan poligami putus karena perceraian, bagaimana pembagian harta bersama ( harta goni)?. Pembagian harta bersama dihitung sejak terjadi perkawinan poligami Istri pertama, kedua, ketiga dan seterusnya dalam hukum Islam maksimal hanya boleh 4 (empat) orang. Perkawinan poligami sah apabila izin dari pengadilan, bagi yang muslim permohonan izin melalui Pengadilan Agama, bagi non mulim permohonan izin ke Pengadilan Negeri. Poligami yang tidak izin dari pengadilan tidak mempunyai kekuatan hukum, jika terjadi masalah hanya dapat diselesaikan diluar pengdilan. Poligami berdasarkan izin dari pengadilan, terjadi masalah dapat diselesaikan melalui pengadilan. Metode penelitian bersifat normatif hanya megunakan data dari hasil penelitian kepustakaan. Kesimpulan dari hasil penelitian, perkawinan poligami diakui hukum apabila izin pengadilan. Sedangkan Poligami tanpa izin pengadilan tidak mempunyai kekuatan hukum, jika terjadi masalah dalam perkawinan tidak dapat diselesaikan melalui pengadilan. Pembagian harta bersama, jika perkawinan putus karena perceraian, harta bersama (gono gini) dibagi dua dihitung sejak terjadi perkawinan poligami, kecuali para pihak menentukan laindalam perjanjian kawin.Keywords: Perkawinan Poligami, Harta bersama (Gono gini) AbstractLaw No. 1 of 1974 on marriage adopts the principle of open monogamy in principle a husband can only have one wife but polygamy is allowed as long as it meets the requirements in the legislation. Polygamous marriages broke up due to divorce, how is the division of joint property (burlap property) ?. The division of joint property is calculated since the polygamous marriage of the first, second, third and so on in Islamic law, the maximum can only be 4 (four) people. Polygamous marriages are legal if permission from the court, for Muslims apply for permission through the Religious Court, for non mulim apply for permission to the District Court. Polygamy without the permission of the court has no legal force, if there is a problem it can only be resolved out of court. Polygamy is based on the permission of the court, any problem can be resolved through the court. Normative research methods only use data from the results of literature research. Conclusion from the results of the study, polygamous marriage is legally recognized if the court permits. While polygamy without court permission has no legal force, if there is a problem in the marriage can not be resolved through the courts. Division of joint property, if the marriage is dissolved due to divorce, the joint property (gono gini) divided in two is counted since the occurrence of the polygamous marriage, unless the parties specify otherwise in the marriage agreement.Keywords: Polygamous Marriage, Common Property (Gono gini)